PENGARUH METODE LATIHAN ZIG-ZAG RUN TERHADAP KEMAMPUAN DRIBBLING SEPAKBOLA - Mochammad Tegar Dwi Nugraha; Hana Astria Nur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the zig-zag run training method ondribbling ability in youth soccer players. The research employed an experimentalmethod with a two-group pretest-posttest design. The sample consisted of 14athletes from SSB Gesit Junior Ciomas U-15, selected using purposive sampling.The instrument used was the zig-zag dribbling test to measure speed, agility, ballcontrol, and dribbling skills. The training program was carried out over 16 sessionswith a frequency of 3–5 times per week. Data analysis showed a significantimprovement in dribbling performance after implementing the zig-zag run training.The average pretest score of 70.28 increased to 78.07 in the posttest. A pairedsample t-test indicated a significance value of 0.000 < 0.05, confirming that the zig-zag run method has a significant effect on dribbling ability. Therefore, the zig-zag run is proven to be an effective training method to enhance the fundamental dribbling skills of youth soccer players.